2019
DOI: 10.2147/cmar.s201177
|View full text |Cite
|
Sign up to set email alerts
|

<p>The relevance between the immune response-related gene module and clinical traits in head and neck squamous cell carcinoma</p>

Abstract: Purpose Head and neck squamous cell carcinoma (HNSCC) is the sixth most prevalent cancer in the world, accounting for more than 90% of head and neck malignant tumors. However, its molecular mechanism is largely unknown. To help elucidate the potential mechanism of HNSCC tumorigenesis, we investigated the gene interaction patterns associated with tumorigenesis. Methods Weighted gene co-expression network analysis (WGCNA) can help us to predict the intrinsic relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 60 publications
5
30
0
Order By: Relevance
“…Therefore, We also investigate the role of immune cells in melanoma, and correlation analysis of the seven prognostic-associated TBC genes with immune cells showed that differential variations of the seven genes regarding immune cells, especially for TBC1D10C ( Figure 8). As reported, TBC1D10C is identified to be related with immune response in head and neck squamous cell carcinoma (27), and artificial neural networks analysis also confirmed the involvement of TBC1D10C in immune response through TCGA (28), suggesting the possible mechanisms of these TBCs in regulation of the immune microenvironment.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, We also investigate the role of immune cells in melanoma, and correlation analysis of the seven prognostic-associated TBC genes with immune cells showed that differential variations of the seven genes regarding immune cells, especially for TBC1D10C ( Figure 8). As reported, TBC1D10C is identified to be related with immune response in head and neck squamous cell carcinoma (27), and artificial neural networks analysis also confirmed the involvement of TBC1D10C in immune response through TCGA (28), suggesting the possible mechanisms of these TBCs in regulation of the immune microenvironment.…”
Section: Discussionsupporting
confidence: 67%
“…Knockdown of TBC1D7 resulted in the activation of mTORC1 signaling, and enhanced cell growth (26). Interests in TBC1D10C are mainly focused on immune response (27,28). Two pieces of literature reported TBC1D19, one showed that TBC1D19 acted upon cell polarity and decreased TBC1D19 expression contributed to the disruption of odontoblast polarity and apoptosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…In another report, weighted gene co-expression network analysis (WGCNA) was used to predict the intrinsic relationship or correlation between gene expression in head and neck squamous cell carcinoma (HNSCC). ARHGAP9 were identified to be used as a biomarker and therapeutic target of HNSCC [38]. These above findings suggested that ARHGAP9 had controversial effects on cell proliferation, migration and invasion among those different cancer types.…”
Section: Discussionmentioning
confidence: 93%
“…Regulation of cell viability of death is likely to be regulated through GIMAP family members in immune cells. And the expression of GIMAP7 gene in normal tissues is higher than that in tumor tissues and may play a regulatory role in the immune response regulation in coordination with other molecules [41]. We speculated that the G deletion (c.826delG, p.Val276Phefs*29) of GIMAP7 gene caused the malfunction and its coordination with other molecules, and nally jeopardized immune response of the body, then the patients in this MD family both showed different symptoms compared to the patients I1 and II1: eg.…”
Section: Discussionmentioning
confidence: 99%